If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (7y + -1) = (11y + 19) Reorder the terms: (-1 + 7y) = (11y + 19) Remove parenthesis around (-1 + 7y) -1 + 7y = (11y + 19) Reorder the terms: -1 + 7y = (19 + 11y) Remove parenthesis around (19 + 11y) -1 + 7y = 19 + 11y Solving -1 + 7y = 19 + 11y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-11y' to each side of the equation. -1 + 7y + -11y = 19 + 11y + -11y Combine like terms: 7y + -11y = -4y -1 + -4y = 19 + 11y + -11y Combine like terms: 11y + -11y = 0 -1 + -4y = 19 + 0 -1 + -4y = 19 Add '1' to each side of the equation. -1 + 1 + -4y = 19 + 1 Combine like terms: -1 + 1 = 0 0 + -4y = 19 + 1 -4y = 19 + 1 Combine like terms: 19 + 1 = 20 -4y = 20 Divide each side by '-4'. y = -5 Simplifying y = -5
| 2x^3-12x^2+18x=0 | | (x+7)(x-6)=(x+7) | | 7a-3=3-3a | | 33+49= | | 4y-70=12y-2 | | 7x-6(x-1)=8 | | x/-5=-26 | | -2=-5+y | | 58y=29(2y+15) | | x-4=-x+4 | | Y=2x^2-5x+9 | | 5b^2-17b-12=0 | | y+-5=-(5+-y) | | 2(x+1)+40=-4x | | (9x+37)=(6x+8) | | 7/8=m+3/8 | | 3+15p-1=8p+12-3p | | 2z^2+11z+1=7 | | 2S^2-s-15=0 | | bx+a=5a-c | | 2x-x+3=15 | | (4/3x)-(1/3)-x+7 | | 1/8=4^8x-4 | | 3(-4b+2)+4b=-22 | | 12x-10+70=180 | | 14+(-2q+5)=-2q+9 | | 4+z+6=-8-12 | | 4+2+6=-8-12 | | 1-3v+10=0 | | 20x^3-14x^2+2x=0 | | X/5-13=-84 | | 8+7(4-5k)=36+5k |